Analysis of Students' Mathematical Communication Skills Based on Verbal-Linguistic Intelligence in Solving Linear Program Problems - Dede Sugiarti; Darhim Darhim; Kusnandi Kusnandi (Eduvest - Journal of Universal Studies, 2024)
Students' ability to communicate, especially in learning mathematics, is still relatively low. Communication skills, especially in solving story problems, are more or less influenced by the intelligence of each student, one of which is verbal linguistic intelligence. This research is a qualitative research with a phenomenological approach. The subjects in this study were grade XI students at Bina Dharma 2 Bandung High School in the 2022/2023 school year totaling 22 students. The sampling technique used Purposefully select. The results showed that students with high linguistic verbal intelligence level were able to answer 5 indicators of mathematical communication ability, students with medium linguistic verbal intelligence level were able to answer 3 indicators of mathematical communication ability, and students with low linguistic verbal intelligence level were able to answer 1-2 indicators of mathematical communication ability.